2011
DOI: 10.3801/iafss.fss.10-1043
|View full text |Cite
|
Sign up to set email alerts
|

A CFD and Experimental Investigation of the Mixing Process in Compartment Fires

Abstract: The mixing of reactants, hot fuel-rich gas and cold air, by a gravity wave, is a complex hydrodynamic process essential in the initiation of hazardous conditions in an under-ventilated compartment fire. The mixing process is first studied by carrying out experiments on a specific enclosure, characterizing the gravity wave by means of particle image velocimetry measurements and fast tomography visualizations. The results are then used to calibrate and validate numerical and CFD models of these experiments. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The velocity profiles for the hot layer at the opening were studied in detail at different time steps [1]. Fleischmann et al [4] first observed a particular shape of the velocity profile.…”
Section: Quantitative Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The velocity profiles for the hot layer at the opening were studied in detail at different time steps [1]. Fleischmann et al [4] first observed a particular shape of the velocity profile.…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…The detailed description of the apparatus, control variables and experimental procedure can be found in Ref. [1].…”
Section: Description Of the Experimentsmentioning
confidence: 99%
See 3 more Smart Citations